Global Depository Receipts in India: boon or bane - S. S. Khakase; B. S. Ronald; T. M. Rathi (Финансы: теория и практика, 2021)
The Global Depository Receipt (“GDR” or “DR”) is a structured financial instrument denominated in foreign currency and Indian companies issue equity shares/securities underlying the GDR to international investors. Many companies have used GDRs for manipulative and fraudulent practices and the Indian regulator, SEBI has penalised them. This paper aims to evaluate the legitimacy of the GDRs and malpractices associated with them and to find if there is any need for reform in the GDR Scheme, to see if the GDRs are beneficial to the economy or are inherently manipulative instruments and looks at the need to reform the laws governing GDR. The authors have employed the methods, literature review and empirical research. The authors have conducted empirical research of the participants in the Indian GDR industry in April and May of 2021 by way of an online Questionnaire and unstructured telephonic interviews. The study results in the author’s conclusion that the GDRs are legitimate instruments but the participants abused the Scheme and led to malpractices. The authors failed to conclude about the need for reforms in the GDR laws. The paper recommends the suitable amendment of the DR scheme with an intention to plug its loopholes and allow it in foreign jurisdictions with the highest compliance requirements while keeping in mind the cost of such compliance.